2022
DOI: 10.3389/fpubh.2022.911593
|View full text |Cite
|
Sign up to set email alerts
|

Self-care practices and associated factors among hypertension patients in public hospitals in Harari regional state and Dire Dawa City administration, Eastern Ethiopia: A multi-center cross-sectional study

Abstract: IntroductionHypertension is a silent killer that causes serious health issues in all parts of the world. Hypertension is a risk factor for cardiovascular disease, stroke, and kidney disease. Self-care practices have been identified as an important component of hypertension management. Despite the government's commitment and the interventions of various stakeholders, the burden of hypertension and its sequel remain unabated. A recent study showed that hypertension self-care practices play a vital role in contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The main characteristics of the included studies are presented in Table 1 included. Of the 18 studies published from 2002 to 2022, nine were conducted in the USA ( 32 40 ), two in Korea ( 41 , 42 ), and one study each was conducted in Mexico ( 43 ), Pakistan ( 44 ), China ( 45 ), Ethiopia ( 46 ), Ghana ( 47 ), Germany ( 48 ), and the UK ( 49 ). The predominant study design was cross-sectional, present in the majority of studies ( 32 , 35 , 39 47 , 49 ), while two were RCTs ( 34 , 38 ), two were cohort studies ( 33 , 36 ), one involved baseline cross-sectional analyses derived from an RCT ( 37 ), and one was a retrospective study ( 48 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The main characteristics of the included studies are presented in Table 1 included. Of the 18 studies published from 2002 to 2022, nine were conducted in the USA ( 32 40 ), two in Korea ( 41 , 42 ), and one study each was conducted in Mexico ( 43 ), Pakistan ( 44 ), China ( 45 ), Ethiopia ( 46 ), Ghana ( 47 ), Germany ( 48 ), and the UK ( 49 ). The predominant study design was cross-sectional, present in the majority of studies ( 32 , 35 , 39 47 , 49 ), while two were RCTs ( 34 , 38 ), two were cohort studies ( 33 , 36 ), one involved baseline cross-sectional analyses derived from an RCT ( 37 ), and one was a retrospective study ( 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 12 studies ( 32 , 35 39 , 41 , 43 45 , 47 , 49 ) the majority of the participants were females, one study reported an equal gender distribution ( 48 ) and one study exclusively involved male participants ( 34 ). Fourteen studies ( 32 39 , 41 46 ) provided data on mean age of the participants, which varied from 41.7 ( 34 ) to 75.0 years ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid having high blood pressure the practice of self-care for hypertension is crucial. Self-care is the intentional, proactive decision and capacity of individuals, families, and communities to actively participate in health promotion and protection, disease prevention, and illness and disability management, either with or without the assistance of a healthcare provider (4). Additionally, by enhancing the self-care behaviors of hypertensive patients, the resulting morbidities, life-threatening complications, and hypertension-related deaths can be decreased (11).…”
Section: Introductionmentioning
confidence: 99%